City of God Christian citizenship in postwar Guatemala - O'Neill, Kevin Lewis, 1977- (Berkeley : University of California Press, 2010)
In Guatemala City today, Christianity isn't just a belief system--it is a counterinsurgency. Amidst postwar efforts at democratization, multinational mega-churches have conquered street corners and kitchen tables, guiding the faithful to build a sanctified city brick by brick. Drawing on rich interviews and extensive fieldwork, Kevin Lewis O'Neill tracks the culture and politics of one such church, looking at how neo-Pentecostal Christian practices have become acts of citizenship in a new, politically relevant era for Protestantism. Focusing on everyday practices--praying for Guatemala, speaking in tongues for the soul of the nation, organizing prayer campaigns to combat unprecedented levels of crime--O'Neill finds that Christian citizenship has re-politicized the faithful as they struggle to understand what it means to be a believer in a desperately violent Central American city. Innovative, imaginative, conceptually rich, City of God reaches across disciplinary borders as it illuminates the highly charged, evolving relationship between religion, democracy, and the state in Latin America.
City of God : an introduction -- Shouldering the weight : the promise of citizenship -- Policing the soul : the cellular construction of Christian citizenship -- Onward, Christian soldier : solitary responsibility and spiritual warfare -- The founding fathers : the problem of fatherhood and the generational imagination -- Hands of love : Christian charity and the place of the indigenous -- Cities of God : international theologies of citizenship -- Disappointment : a conclusion.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Evangelistic work -- Guatemala -- Guatemala; Evangelistic work -- Pentecostal churches; Pentecostal churches -- Missions -- Guatemala -- Guatemala; Christianity and politics -- Guatemala -- Guatemala; Guatemala (Guatemala) -- Religion; RELIGION / Messianic Judaism; Electronic books